Imagens Narradas: educação e vida em duas (e mais) ficções (Revista Apotheke, 2022)
This paper addresses the connection between education and life, through one situation of the teaching and learning of art created in the interwoven of the two fictions: “Having an experience” by John Dewey and “Where is the friend's home?” by Abbas Kiarostami.
Keywords: Art; education; life; images; fictions